FOMO as mediator of SMM and e-WOM on intention - Galuh Mira Saktiana (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2026)
This research aims to explore the phenomenon of FOMO in relation to purchase intent, social media marketing, and EWOM. FOMO arises when individuals feel that their quality of life will improve if they do not miss out on information, trends, events, or experiences that are currently happening. This study will also examine FOMO as a mediating factor between SMM and EWOM and the intention to purchase. This study will apply TAM Theory, in which the research model is constructed using variables that reflect technology adaptation in its application. The research design was quantitative and cross-sectional. The research sample was selected using purposive sampling, specifically by applying the following criterion: social media users who had seen Sensatia Botanicals advertisements, resulting in 201 respondents. Validity testing included discriminant and convergent validity. After that, reliability testing is needed to assess the questionnaire's indicators. SEM-PLS was used to test hypotheses in this research. The research concludes that SMM has no direct effect on purchase intention, whereas FOMO fully mediates this effect. In the effect of EWOM on intention to purchase, FOMO acts as a partial mediator because EWOM has a direct effect on intention to purchase